Enhanced Acquisition and Retention of Conditioned Eyeblink Responses in Veterans Expressing PTSD Symptoms: Modulation by Lifetime History of Mild Traumatic Brain Injury - Handy, Justin D.; Wright, W. Geoffrey; Haskell, Amanda; Servatius, Labeeby; Servatius, Richard J. (Frontiers in Behavioral Neuroscience, 2020)
Enhanced acquisition of eyeblink conditioning is observed in active duty military and veterans expressing PTSD symptoms (PTSD+) and those expressing temperamental vulnerabilities to develop PTSD after traumatic experiences, such as behaviorally inhibited temperament. There is a growing literature showing persistent cerebellar abnormalities in those experiencing mild traumatic brain injury (mTBI+) as well as linkages between mTBI and PTSD. With the dependency of eyeblink conditioning on cerebellar processes, the impact of mTBI on eyeblink conditioning in veterans expressing PTSD is unknown. The present study assessed eyeblink conditioning in veterans during two sessions separated by one week. With a focus on the accelerated learning of veterans expressing PTSD, training utilized a protocol which degrades learning through interspersing conditioned stimulus (CS) exposures amongst delay-type trials of CS and unconditional stimulus (US) co-terminating trials. Faster acquisition of the eyeblink conditioned responses (CR) was observed in PTSD during Week 1. The Week 2 assessment revealed an interaction of mTBI and PTSD, such that asymptotic performance of PTSD+ was greater than PTSD- among mTBI- veterans, whereas these groups did not differ in mTBI+ veterans. To further examine the relationship between enhanced sensitivity to acquire eyeblink conditioning and PTSD, cluster analysis was performed based on performance across training sessions. Those with enhanced sensitivity to acquire eyeblink conditioned responses expressed more PTSD symptoms, which were specific to Cluster C symptoms of avoidance, in addition to greater behavioral inhibition. These results support the continued investigation of the conditioned eyeblink response as a behavioral indicator of stress-related pathology.